Impact of Opioid Dependence on Economic Burden of Hospitalizations Among Patients Undergoing Lumbar Fusion: Insights from the National Inpatient Sample. (16th November 2020) - Bydon, Mohamad; Alvi, Mohammed A; Berg, Jake; Zreik, Jad; Wahood, Waseem; Yolcu, Yagiz U; Goyal, Anshit; Jeffery, Molly; Sebastian, Arjun
Abstract: INTRODUCTION: Rates of opioid use in the United States have steeply risen over the past couple of decades leading to increases in societal costs. Current literature is scarce on the impact of preoperative chronic opioid dependence on economic burden with immediate hospitalizations in the form of longer length of stay, non-routine discharge and hospitalization costs METHODS: The National Inpatient Sample (NIS) was queried for patients undergoing PLF for degenerative disc disease between 2012 and the third quarter of 2015. After 1:3 propensity score matching, multivariable conditional logistic regression was performed to assess the association between opioid dependance and length of stay, non-home discharge, and hospital charge RESULTS: A total of 114, 507 patients undergoing PLF were identified, of which 644 had a diagnosis code for opioid dependence/abuse. opioid dependence of abuse comorbidity also had longer average length of stay (4.55 vs 3.30 days, P < .001), higher average cost of hospitalization (37, 712.98 vs 30, 650.46, P < .001), and increased rates of non-routine discharge (46.89% vs 32.71%, P < .001) as compared to those without the comorbidity. On multivariable analysis, opioid dependence/abuse was found to be significantly associated with increased hospital costs (OR = 1.78, 95% CL: 1.23-2.58, P = .002), length of stay (OR: 1.53; 95% CI: 1.16-2.00; P = .003), and non-routine discharge (OR: 1.74; 95% CI: 1.34-2.26; P < .001). CONCLUSION: Our findings from a national database contributes to the growing literature on the economic impact of opioid dependence. In particular, our analyses indicate that among patients undergoing routine spinal fusion, preoperative opioid dependence may be associated with increased burden on healthcare economics in the form of increased length of stay, higher rate of non-routine discharge and higher hospitalization costs.